The Influence Of Human Resource Quality, Professionalism And Career Development On Employee Performance In The Personnel And Human Resources Development Agency Of Bengkulu City - Marlia Prameswari; Ratnawili Ratnawili (Penerbit Jurnal Indonesia, 2024)
This study aimed to determine of HR Quality, Professionalism and Career Development on Employees' Performance at the Bengkulu City Personnel and Human Resources Development Agency. The population of this study were employees of the Personnel and Human Resources Development Agency of Bengkulu City. This study used the saturated sampling method. This study used observation and questionnaire. The data analysis techniques of this study used instrument testing, classical assumption testing, analysis of respondent responses, multiple linear regression analysis, hypothesis testing and analysis of the coefficient of determination. The results of the study show that HR Quality has a positive and significant effect on employees' performance. Professionalism has a positive and significant effect on employees' performance. Career Development has a positive and significant effect on employees' performance. Simultaneously, the quality of human resources, professionalism and career development have effect on employees' performance at The Bengkulu City Personnel and Human Resources Development Agency.